2021
DOI: 10.3390/insects12040332
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Spent Coffee and Donuts by Black Soldier Fly (Hermetia illucens) Larvae into Potential Resources for Animal and Plant Farming

Abstract: Nutritionally unbalanced organic waste can be converted into potential resources for animal and plant farming by culturing black soldier fly (Hermetia illucens) larvae (BSFL) and prepupae (BSFP). BSFL and BSFP are rich sources of protein and lipids, while the leftover excrement called “frass” can be used as an organic fertilizer. Using readily available resources, BSFL were cultured on spent coffee, donut dough or an equal blend for 35 days. Survival, productivity, daily pupation and biochemical composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…In addition to proteins, larvae crude fat was influenced by density and scale, in addition to an interaction between the two factors. Crude fat was shown to increase at higher larval density, which also supports the findings of Barragan-Fonseca et al [29] and Fischer et al [63], where BSFL grown in lower densities in small-scale experiments had lower crude fat. Based on the results presented in this study, it can be assumed that the availability of carbohydrates and fats in the substrate may not play a major role in fat accumulation in the larvae.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to proteins, larvae crude fat was influenced by density and scale, in addition to an interaction between the two factors. Crude fat was shown to increase at higher larval density, which also supports the findings of Barragan-Fonseca et al [29] and Fischer et al [63], where BSFL grown in lower densities in small-scale experiments had lower crude fat. Based on the results presented in this study, it can be assumed that the availability of carbohydrates and fats in the substrate may not play a major role in fat accumulation in the larvae.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the results presented in this study, it can be assumed that the availability of carbohydrates and fats in the substrate may not play a major role in fat accumulation in the larvae. Fischer et al [63] have suggested that a trade-off between crude protein and crude fat might have occurred in their experiment, which was also the case in other studies [19]. This phenomenon can also be observed in a bigger scale experiment done by Scala et al [34] and the present study, as the fat content was the lowest in treatments with higher crude protein, and it seems to be negatively correlated with protein availability for the larvae, and not dependent on substrate carbohydrate or fat availability.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is due to some specific growth-inhibitory substance of this substrate is under question. Fischer et al tested the performance of BSF larvae on sole and blends of spent coffee grounds and donuts where they proved that the former developed the smallest [41]. SCG contains various nitrogencontaining substances such as caffeine, trigonelline, free amines and amino acids [42].…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid content of BSFL is not altered greatly by their diet, despite being fed diets with vastly different amino acid profiles. Moreover, the amino acid profile of BSFL is similar or even superior to soybean meal, which is often the dominant protein in aquafeeds (Fischer et al 2021a , b ). On the other hand, the proximate and fatty acid composition of BSFL tends to be more influenced by their food source.…”
Section: Introductionmentioning
confidence: 99%